2021
DOI: 10.3390/jmse9020129
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and Distribution of Cigarette Butts on Coastal Environments: Examples from Southern Spain

Abstract: Litter on beaches is one of the most difficult problems in coastal management and every year, much efforts and public money are invested to try to alleviate and solve the problem. Cigarette butts (CB) are among the most widespread abandoned personal items in the world. In Spain, they are found on all types of beaches, where they are discarded by beach users; however, rivers and streams can also deposit CB on shores. This paper analyses the abundance of CB on different beaches in Southern Spain in order to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 61 publications
(94 reference statements)
1
4
0
Order By: Relevance
“…This finding is consistent with another study where no cigarette butts were found on remote beaches from the Moroccan Mediterranean coast (Maziane et al, 2018). On other remote beaches, cigarette butts were observed in a few surveys (Katarzytėet al, 2020;Asensio-Montesinos et al, 2021). On the Ecuadorian village beaches surveyed here, the low number of cigarettes is similar to that reported in the same places assessed by Gaibor et al (2020).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with another study where no cigarette butts were found on remote beaches from the Moroccan Mediterranean coast (Maziane et al, 2018). On other remote beaches, cigarette butts were observed in a few surveys (Katarzytėet al, 2020;Asensio-Montesinos et al, 2021). On the Ecuadorian village beaches surveyed here, the low number of cigarettes is similar to that reported in the same places assessed by Gaibor et al (2020).…”
Section: Discussionsupporting
confidence: 92%
“…Other studies focused on a single type of litter. For instance, the abundance of cigarette butts in touristic beaches has been investigated due to the potential release of highly toxic chemicals, such as heavy metals, aliphatic and unsaturated hydrocarbons, polycyclic aromatic hydrocarbons, among others ( Asensio-Montesinos et al, 2021 ; Soleimani et al, 2022 ). In the case of PPE, the most recent studies focused solely on this type of litter due to its unique characteristics (e.g., structure, components, and release of contaminants) ( Kutralam-Muniasamy et al, 2022 ; Sullivan et al, 2021 ) and unprecedented occurrence ( Cordova et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…This is largely due to the prevalent misperception that cigarette butts are biodegradable and made of plastic. Similarly, another study concluded that the following aspects are favoring cigarette butt buildup on Spain's southern coast: seasonality and number of beach visitors, beach typology (remote, rural, village, or urban areas), and the frequency of cleaning activities conducted [24].…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 96%